2013
DOI: 10.4236/pp.2013.42036
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Estrogenic Activity of Pueraria (Kudzu) Flower Extract and Its Major Isoflavones Using ER-Binding and Uterotrophic Bioassays

Abstract: Pueraria flower extract (PFE) is a hot water extract of the Kudzu flower (Pueraria thomsonii). Tea made from driedKudzu flower is widely used in China, and PFE is utilized as a nutritional supplement in Japan. PFE contains unique isoflavones such as 6-hydroxygenistein 6,7-di-O-glucoside (6HGDG), tectorigenin 7-O-xylosylglucoside (TGXG), and tectoridin. 6HGDG is known to be metabolized into 6-hydroxygenistein, and TGXG and tectoridin are known to be metabolized into tectorigenin in the digestive tract. Isoflavo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 17 publications
(21 reference statements)
0
6
0
Order By: Relevance
“…Our results showed that PBE did not increased uterine‐weight in OVX mice. Uterine weight gain indicates an excess intake of estrogenic compounds, as observed when dietary supplements containing estrogenic compounds (soy isoflavones 1,000 mg/kg body weight) were ingested by female mice (Kamiya, Takano, Kido, & Matsuzaka, 2013). The administration of Pueraria mirifica (660 mg/kg BW/day) has been reported that pronounced inflammation of the uterine wall and increase in mammary adenocarcinoma incidence in postpubertal rats.…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed that PBE did not increased uterine‐weight in OVX mice. Uterine weight gain indicates an excess intake of estrogenic compounds, as observed when dietary supplements containing estrogenic compounds (soy isoflavones 1,000 mg/kg body weight) were ingested by female mice (Kamiya, Takano, Kido, & Matsuzaka, 2013). The administration of Pueraria mirifica (660 mg/kg BW/day) has been reported that pronounced inflammation of the uterine wall and increase in mammary adenocarcinoma incidence in postpubertal rats.…”
Section: Discussionmentioning
confidence: 99%
“…Uterine weight in the SI20 treatment group was higher than in OVX mice, but was still lower than in the sham mice (Table 2). Kamiya et al reported that SI products induced an increase in uterine weight at doses of 500 mg/kg in OVX rats, whereas the kudzu flower extract did not cause it, and the ER-binding affinity of the related compound tectorigenin was approximately 0.02–0.04 that of genistein in vitro [17]. Moreover, our study demonstrated that the femoral BMD and trabecular BMD of the distal femur were higher in OVX mice in the SI20 treatment relative to untreated OVX mice, and that the BMDs of mice in the PFI20 treatment did not exhibit a similar response.…”
Section: Discussionmentioning
confidence: 99%
“…Kudzu flower extract, primarily derived from Pueraria thomsonii , contains isoflavones. Isoflavones induce weak oestrogen-like effects and are classified as phytoestrogens [17]. Thus, kudzu flower extract might be used as an alternative to oestrogen-based menopausal therapies by menopausal women, who are likely to take it concomitantly with other medicines.…”
Section: Introductionmentioning
confidence: 99%
“…Phytoestrogens, specifically isoflavones, are plants considered chemoprotective, with estrogen-like properties compounds, due to their conformational similarity to -estradiol, and can be used as an alternative therapy for hormonal disorders [4,5]. Isoflavones are phenols that enable the activation of estrogen receptors (ER) and the regulation of gene expression in target tissue cell nuclei.…”
Section: Introductionmentioning
confidence: 99%